2022
DOI: 10.1021/jacs.1c10908
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Furfural/5-Hydroxymethyl Furfural Oxidation to Furoic Acid/Furan-2,5-dicarboxylic Acid with H2 Production Using Alkaline Water as the Formal Oxidant

Abstract: Furfural and 5-hydroxymethyl furfural (HMF) are abundantly available biomass-derived renewable chemical feedstocks, and their oxidation to furoic acid and furan-2,5-dicarboxylic acid (FDCA), respectively, is a research area with huge prospective applications in food, cosmetics, optics, and renewable polymer industries. Water-based oxidation of furfural/HMF is a lucrative approach for simultaneous generation of H 2 and furoic acid/FDCA. However, this process is currently limited to (photo)electrochemical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 55 publications
0
46
0
Order By: Relevance
“…Catalytic H2 generation from biobased aldehydes can also be accompanied by the production of valuable by-products, such as carboxylic acids. In the past years, the transformation of aldehydes to carboxylic acids along with H2 evolution was reported from several non-Faradaic reactions, including base-, 17,18 heterogeneous-, [19][20][21] and homogeneous [22][23][24][25] -catalyzed processes (RXN 3). However, these reactions generally require a high concentration of base (>>1 M OH − ) or elevated temperature (>100 ℃) with both aldehyde and H2O as proton sources in the formation of H2.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic H2 generation from biobased aldehydes can also be accompanied by the production of valuable by-products, such as carboxylic acids. In the past years, the transformation of aldehydes to carboxylic acids along with H2 evolution was reported from several non-Faradaic reactions, including base-, 17,18 heterogeneous-, [19][20][21] and homogeneous [22][23][24][25] -catalyzed processes (RXN 3). However, these reactions generally require a high concentration of base (>>1 M OH − ) or elevated temperature (>100 ℃) with both aldehyde and H2O as proton sources in the formation of H2.…”
Section: Introductionmentioning
confidence: 99%
“…Chem. A, 2022, 10,19963 These catalysts were reported to effectively catalyze the oxidation of HMF to FDCA in strong alkali electrolyte via path II (Scheme 1). Interestingly, DFF is also a high value-added platform chemical and can be used either as a monomer, or as starting material in the synthesis of furan-urea resins, foams, binders, and pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
“…24a and b). 80 Furfural and HMF are bio-based renewable feedstocks, and their oxidation products are important for the implementation of future green chemical industry. 81,82 It was found that while in the presence of other pyridine-based pincer complexes furfural and HMF degraded to unidentifiable polymers, the acridine-based complexes selectively oxidized them with high yields (495%), while suppressing decomposition.…”
Section: Deaminative Oxidation Of Amines To Acidsmentioning
confidence: 99%